A Document Analysis on the Efficacy and Ethical Considerations of Online Counseling - William Jo Se Billote; Marie Fe Escoto; Ryan Ponce; Trixie Elaine Ponce; Eliseo Pama; Rizzalie Morne Montoya; Joan Quibal; Aljon Quiloan; Marilys Ponce; Marianne Jean Adam (Philippine Association of Institutions for Research, Inc., 2021)
The current situation brought about by the pandemic and technological advancements has resulted in a significant rise in the number of people who participate in online settings. Research into online counseling practice is significant as it is given the relative newness of the techniques. With this trend in guidance and counseling, the research aimed to find out the different concerns and issues when providing online counseling and online therapy's efficacy. The research design involved utilizing the qualitative research method in addressing the research question, and document analysis was employed. This research's specific documents include outcomes-based studies, process studies, and self-report studies in guidance and counseling. After examining and analyzing literature from the three categories of study, online therapy appeared to be clinically efficacious. Online counseling was more convenient and less inhibition in disclosing confidential issues during online sessions.